COMPRESSION STRUCTURES IN THE PACIFIC BETWEEN THE CLARION AND CLIPPERTON FRACTURE ZONES - Korsakov O.D.; Pilipenko A.I. (My University, 1989)
Since the middle of the 1970's, the Yuzhmorgeologiya Survey had been systematically studying the part of the Northeast Pacific Basin near the equator by the methods of seismoacoustic profiling and echo sounding, combined with magnetometry, photoprofiling and bottom dredging. The Pacific Ocean floor in the region between the Clarion and the Clipperton Fracture Zones has been investigated most thoroughly so far. Much of it has been covered in large-scale areal seismoacoustic surveys. The results of seismoacoustic profiling and echo sounding have provided detailed information on the morphostructure of the ocean floor and acoustic basement surface in this region. Geological interpretation of the seismoacoustic data on the Clarion-Clipperton Fracture Zone region indicates significant differential mobility of the oceanic crust and, consequently, its internal tectonic layering. The presence of tectonic compression and extension zones is due to differential movement of the crustal blocks. These data also indicate that the crust west of the East Pacific Rise is undergoing tectonic compression.